2021
DOI: 10.2991/ahsr.k.210115.111
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Progressive Mobilization on Pneumonia and Decubitus Occurrences in Critical Patients Using Mechanical Ventilator

Abstract: Background: The short-term impact felt by critically ill patients and ventilators are Ventilator-Associated Pneumonia (VAP), which is added to the health mechanism due to muscle weakness and the occurrence of pressure sores or decubitus. Prevention of pneumonia in intubation patients is crucial because it can prevent hospital-acquired or nosocomial infections, which is a severe complication. Extensive skin destruction or pressure can cause depression in the blood supply and tissue damage. Decubitus will distur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
0
0
2
Order By: Relevance
“…American Association of Critical Care Nurses (AACN) memperkenalkan intervensi mobilisasi progresif yang terdiri dari beberapa tahapan: Head of Bed (HOB), latihan Range of Motion (ROM) pasif dan aktif, terapi lanjutan rotasi lateral, posisi tengkurap, pergerakan melawan gravitasi, posisi duduk, posisi kaki menggantung, berdiri dan berjalan (Mokorimban & Chayati, 2021).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…American Association of Critical Care Nurses (AACN) memperkenalkan intervensi mobilisasi progresif yang terdiri dari beberapa tahapan: Head of Bed (HOB), latihan Range of Motion (ROM) pasif dan aktif, terapi lanjutan rotasi lateral, posisi tengkurap, pergerakan melawan gravitasi, posisi duduk, posisi kaki menggantung, berdiri dan berjalan (Mokorimban & Chayati, 2021).…”
Section: Pendahuluanunclassified
“…Pada sistem respirasi mobilisasi berfungsi meningkatkan frekuensi dan kedalaman pernapasan, meningkatkan ventilasi alveolar, menurunkan kerja pernapasan dan meningkatkan pengembangan diafragma. Sehingga pemberian mobilisasi diharapkan mampu meningkatkan transport oksigen ke seluruh tubuh (Mokorimban & Chayati, 2021).…”
Section: Pembahasanunclassified
“…Research conducted by Needham et al showed that patients treated in the ICU experience hemodynamic imbalances, one of which is caused by bed rest for a long time. One of the efforts made by nurses to improve the functional and hemodynamic status of patients is to mobilize (Mokorimban, (2021).…”
Section: Introductionmentioning
confidence: 99%
“…Mobilization interventions performed on patients in the ICU have a good effect, including increasing muscle strength, reducing the patient's length of stay, reducing the patient's dependence on delirium, and accelerating the weaning process in patients who are on a ventilator (Mokorimban, 2021). Research conducted by Rebbel et al showed the results that mobilization had an effect on the hemodynamic status of patients, including breathing, blood pressure, pulse, and temperature.…”
Section: Introductionmentioning
confidence: 99%